ETHNIC POWER SHARING: THREE BIG PROBLEMS - Donald L Horowitz (Jurnal Ilmiah Peuradeun, 2014)
Societies are severely divided by ethnicity, race, religion, language, or any other form of ascriptive affiliation, ethnic divisions that make democracy difficult, because they tend to produce ethnic parties and ethnic voting. Two commonly proposed methods of amelioration are called consociational and centripetal. Three problems derive from these proposals: The first concerns the adoptability of either of the two principal prescriptions. Under what conditions can either be adopted? The second relates to a possibility inherent in centripetal regimes: the potential degradation of the electoral arrangements that sustain the interethnic coalition. The third, derives from a common consequence of the adoption of a consociational regime: Where robust guarantees, including minority vetoes, are adopted, immobilism is a strong possibility, and it may be very difficult to overcome the stasis that immobilism can produce. By examining these three problems, we can uncover some of the frailties inherent in both of the common prescriptions.